# Beam Bending Equation Proof: Simply Supported Point Load

The equations for beam bending, reactions, slope and deflection will be found using Macaulay Brackets and the values from the diagram below. Macaulay brackets are represented with square brackets ("[" and "]"), when the value within the brackets is negative, then the bracketed expression is given a value of zero. Macaulay brackets are used to turn individual expressions "on" or "off", depending at what point along the beam you are interested. For more information on Macaulay brackets, please follow this link.

A useful tool for calculating bending moments, shear forces, deflection and slope for this beam and load combination is contained on this website at this location.

$$\text{From vertical equilibrium}$$ $$\qquad R_{A} + R_{B}= P$$ $$\text{From moment equilibrium}$$ $$\qquad R_{A} = Pb/L$$ $$\text{Moment expression using Macaulay Brackets}$$ $$\qquad M_{x} = - R_{A}x + P[x-a]$$ $$\qquad EI \frac{d^2v}{dx^2} = M_{x} = - R_{A}x + P[x-a]$$ $$\qquad EI \frac{dv}{dx} = - \frac{R_{A}x^2}{2} + \frac{P}{2}[x-a]^2 + A$$ $$\qquad EI v = - \frac{R_{A}x^3}{6} + \frac{P}{6}[x-a]^3 + Ax + B$$ $$\text{Check the boundary conditions to find constants } A \text{ and } B$$ $$\text{At } x = 0, v = 0$$ $$\qquad \text{Therefore, } B = 0$$ $$\text{At } x = L, v = 0$$ $$\qquad \text{Therefore, }$$ $$\qquad 0 = - \frac{R_{A}L^3}{6} + \frac{P}{6}(L-a)^3 + AL$$ $$\qquad \text{Using the solutions, } R_{A} = Pb/L \text{ and } L-a = b$$ $$\qquad A = \frac{PbL}{6} - \frac{Pb^3}{6L}$$ $$\qquad A = \frac{Pb}{6L}(L^2 - b^2)$$ $$\text{Therefore,}$$ $$\qquad \text{Reactions,}$$ $$\qquad\qquad R_{A} = Pb/L$$ $$\qquad\qquad R_{B} = P - R_{A}$$ $$\qquad \text{Moment expression,}$$ $$\qquad\qquad M_{x} = - \frac{Pbx}{L} + P[x-a]$$ $$\qquad \text{Slope equation,}$$ $$\qquad\qquad EI \frac{dv}{dx} = - \frac{Pbx^2}{2L} + \frac{P}{2}[x-a]^2 + \frac{Pb}{6L}(L^2 - b^2)$$ $$\qquad\qquad \frac{dv}{dx} = \frac{P}{12EI}(-6bx^2 + 6[x-a]^2+ \frac{2b}{L}(L^2 - b^2))$$ $$\qquad\qquad \frac{dv}{dx} = \frac{P}{6EIL}( b(L^2 - b^2 - 3x^2)+3L[x-a]^2)$$ $$\qquad \text{Deflection equation,}$$ $$\qquad\qquad EI v = - \frac{Pbx^3}{6L} + \frac{P}{6}[x-a]^3 + \frac{Pbx}{6L}(L^2 - b^2)$$ $$\qquad\qquad v = \frac{P}{6EI}(-\frac{bx^3}{L} + [x-a]^3+\frac{bx}{L}(L^2 - b^2))$$ $$\qquad\qquad v = \frac{P}{6EIL}(bx(L^2 - b^2 -x^2)+L[x-a]^3)$$